Teacher as a Participative Leader. Participative Leadership in Ruth C. Cohn's Theme-Centred Interaction (TCI) - Kazimiera Wawrzynów (Nicolaus Copernicus University in Toruń, 2012)
In the Theme-Centred Interaction, special attention is given to the management of group processes, which are present in the school environment. TCI differs not only from all forms of educational activities that are devoid of group leadership, or merely moderated, but also from the learning programs with predetermined methods and media. What is specific for group leadership within TCI is the encouragement to learn and communicate. The teachers who lead a group of students according to TCI are expected to get involved in the group interaction process together with the students. They consciously and actively take part in the processes that they direct. Participative leadership also means that in the course of directing a group, leaders reveal their opinions and viewpoints. Participative leadership in TCI groups occurs when a teacher constantly moves along the border between his existential involvement in the subject and the group processes, but at the same time he clearly understands his own function of a leader, which is understood not as a status but as a commitment to the group. Participative leadership according to TCI requires long practice and, if possible, professional training. The task of a group leader, amongst others, is to watch over "the dynamic equilibrium" (dynamische Balance in German) between all the factors that are still used in live group processes and that join one another. Participative leadership on the methodical and scientific level opens up the way for investigation of participation, which should be further developed.